Hurricanes! - Hood, Susan, 1954-; Weather Channel (Television station : Atlanta, Ga.) (New York, N.Y. : Simon Spotlight, 1998)
Provides information and safety tips relating to hurricanes and discusses notable examples from the past.
Includes index.
Keywords: Hurricanes -- Juvenile literature; Hurricanes